The Journal of V. N. Karazin Kharkiv National University. – 2009. - № 879. Series Medicine. – Issue 18 - (:unkn) unknown (Харків : Харківський національний університет імені В. Н. Каразіна, 2009)
Journal contains articles about topical issues of modern experimental and clinical medicine
Вісник Харківського національного університету імені В. Н. Каразіна. – 2009. - № 879. Cерія Медицина. – Вип. 18
Keywords: Health Organization; Fundamental Research; Clinical Research; Reviews; Clinical Practice; Lectures; Medical Law; Ecology and Health; Philosophy of Medicine